Anxiety of Health Workers in the Prevention and Management of Covid-19 in Sidrap Regency (Unnes Journal of Public Health, 2020)
The spread of Covid-19 disease has reached epidemiological criteria which need to be declared a pandemic because it has infected more than 100,000 people in 100 countries. The purpose of this study was to determine the criteria for anxiety levels in health workers in the prevention of covid-19. In carrying out their duties, most of health workerd experienced anxiety due to lack of personal protective equipments and family safety. This study uses a a cross sectional survey design and cluster random sampling techniques with 80 respondents. The results showed that the average health workers 52 respondets (65.0%) had experienced mild anxiety, 11 respondents (13.8%) had experienced moderate anxiety, and 2 respondents (2.5%) had experienced severe anxiety and 15 respondents (18.8%) who didn’t experienced anxiety.The contributing factor is the lack of personal protective equipment, so the health workers worried to transmited the corona virus to their family. They also felt stigmatized because they felt related to patients infected by the virus. In addition, the patients honesty when visited health services, many of them keep it a secret of a visit history to the plague area or areas that have suffered many cases of Covid-19.